Relationship between Learning Patterns Through Online Media and Stress During the COVID-19 Pandemic in Middle School Students - Ika Wahyudi Ningsih; Edi Sukamto; Gajali Rahman (Formosa Journal of Applied Sciences, 2023)
The purpose of this research is to find out whether there is a relationship between learning patterns through online media and stress during the Covid-19 pandemic for students at SMP Negeri 03 Gunung Tabur in Berau Regency. This study used a design with a cross-sectional design approach. The sample in this study was carried out by means of a total sample of 230 students at SMP Negeri 3 Gunug Tabur. The relationship between the independent variables and also the dependent variable uses the Chi Square test analysis method. The results of the analysis using the chi square test obtained a p value = 0.006 (p value <0.05) with an OR of 2.431. There is a relationship between learning patterns through online media and stress during the Covid-19 pandemic for students at SMP Negeri 03 Gunung Tabur in Berau Regency.